Valoración de un seguro de vida mediante opciones exóticas; Life insurance valuation using exotic options - Gabriela Pesce; Gastón Milanesi; Emilio El Alabi; Joaquín Menna (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– This paper presents the analysis and valuation of an individual, temporary, and leveled-prime life insurance. It starting point is an analogy between contract rules and a financial exotic option. In particular, a cash or nothing option. Several cases are presented from a person with different age and gender, and sensitivity to different probability distributions are tested using Monte Carlo simulation. All cases are adjusted to Argentinean recent data in order to estimate exercise prices, main variable to estimate the contract value. Prime market values used on this work are more than double than the theoretical value found on the exotic option while comparing them to identical contract conditions such as insured amount, time frame and demographic conditions of the individual.
Keywords: G13; G22; C15; 330; exotic option; life insurance; digital option; exercise probability